The effect of anti-nausea wristbands and STW-5 in children suffering from dyspepsia – a randomized double-blind placebo-controlled pilot-study - Légeret, Corinne; Ludyga, Sebastian; D’Aujourdhui, Muriel; Schneider, Selina; Hagmann, Sarah; Acket, Annemarie; Köhler, Henrik; Furlano, Raoul (Klinische Pädiatrie, 2025)
Functional dyspepsia (FD) is common in children and refers to discomfort in the epigastric/duodenal region, which cannot be explained by structural or biochemical abnormalities. Since the pathophysiology is still not fully understood, no guidelines in terms of treatment do exist.The aim of this study was to compare the therapeutical effect of plant extracts (STW-5) and acupressure in children with functional dyspepsia.This is a randomized, double-blind placebo-controlled trial. Before and after the allocated intervention of four weeks, participants had to fill in a cross-cultural validated questionnaire consisting of 52 questions to assess quality of life, as well as the extent of their discomfort (using a standardized visual analog scale (VAS)).33 patients were included in the study: 12 male and 21 female with an average age of 12.09 years (range: 7–17 years). Symptoms improved after four weeks of intervention in most treatment-groups: By 68% in children, who received STW-5, by 40% in the wristband (WB)- group and by 35% in the wrist-band-Placebo-group (WBPL). Patients receiving STW-5- Placebo showed even an increase of symptoms.This double-blind, placebo-controlled pilot study showed, that STW-5 and/or anti-nausea wristbands are a cheap and effective option to treat children and teenagers suffering from functional dyspepsia.
Keywords: children; functional dyspepsia; anti-nausea bands; Placebo